Indonesia’s External Debt Odyssey: Impact of Fiscal and Political Changes from 1999 to 2023 - Utama, M. Munip; Chalid, Pheni (Universitas Airlangga, 2024)
This study aims to identify the factors influencing Indonesia’s dependence on external debt. The data utilized in this research consist of a time series covering the period from 1999 to 2023 on a quarterly basis. The endogenous variable in this study is Indonesia’s external debt, while the exogenous variables encompass fiscal deficit, tax income, inflation rates, and the volatility index. The instrumental variables employed include lags of both endogenous and exogenous variables. Additionally, dummy variables are incorporated for the four government regimes. Two estimation models consistently present a coherent picture. The dynamic fixed-effect model utilized in this research indicates that dependence on external debt is a legacy of previous governments in both models. Historical factors from prior external debt play a pivotal role in determining Indonesia’s external debt level, and the impact of current and past tax revenue periods contributes positively to Indonesia’s ability to increase debt, even though only current tax revenue has a significant impact. Theoretically, fiscal deficits and global economic instability are considered important indicators, but this study found that neither has a consistent and significant influence on Indonesia’s external debt. Controlling inflation rates is also crucial in curbing borrowing behavior from foreign entities. Government regime transitions do not appear to contribute significantly to the management of external debt. Based on the R-squared adjustment test and the Wald test, it is revealed that the exogenous variables, instrumental variables, and dummy variables in this study effectively explain the variation of the endogenous variable.